Fighting Fake Facts - Seitz, Peter; Eisenegger, Mark; Bergman, Manfred Max (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The scientific method, known for its systematic and rigorously approach, has yielded countless discoveries and essential technologies that enhance our lives, fostering ease, productivity, and comfort. Yet, many of these discoveries and technologies have facilitated the dissemination of false and potentially harmful information-the realm of fake facts. The distortion of information, encompassing misinformation, disinformation, and malinformation, poses a threat to democratic societies and the core of scientific progress. Consequently, the scientific community must explore why fake news resonates, identify detection strategies, and develop effective countermeasures. The years 2020 and 2021, dominated by the Covid-19 pandemic, underscored the impact of fake news. Conspiracy theories, dangerous pseudo-therapies, and anti-vaccine movements thrived, highlighting the urgency of addressing false information. The collection of articles in this book cover key topics related to fake facts and fake news, aiming to enhance understanding of their impact and to counter them using scientific principles.